Avances en Internet de las Cosas (2019)
The Internet of Things continues to set the pace of many aspects of the scientific and technological development worldwide. Moreover, it is expected to do so, at least, for the next ten years, according to forecasts that predict trillions of devices connected to the Internet [1]. In addition to influencing different factors of people’s daily lives, this new vision of the world poses a series of challenges and opportunities that have an effect on general aspects of the economy and politics.